Penerapan model discovery learning untuk meningkatkan keterampilan membaca pemahaman pada peserta didik kelas IV sekolah dasar - Suci Rahmawati; Jenny Indrastoeti Siti Poerwanti; Chumdari Chumdari (Universitas Sebelas Maret, 2024)
The studys goals are: 1) to represent the appliance of Discovery Learning model in developing reading comprehension skills; 2) to developing reading comprehension skills with the Discovery Learning model. Classroom Action Research (CAR) is a type of qualitative research. Each cycle contains the stages of devising, application, research, and consideration. The subjects were 17 fourth grade students, consisting of 10 male scholars and 7 female scholars, and teachers. The data assortment systems used were observation, interviews, documentation, and tests with source and technique triangulation validity tests. The Miles and Huberman model was used for data analysis. The conclusions showed that students' reading comprehension skills at pre-action reach an average of 37.7 with 7.7% classical completions. Cycle 1 reach an average of 70.4 with 62.5% classical completions. Cycle 2 obtained an average of 87 and 100% classical completions. Based on the fact, it can be achieved that fourth grade students reading comprehension skills of SD Negeri Banaran 04 Grogol, Sukoharjo in the 2023/2024 can advance by using Discovery Learning model.